Effect of high-beta versus gamma binaural beat exposure on immediate and delayed recall - Grobler, Etienne (Department of Psychology, 2025)
In this study, I investigate the effect of binaural beats on immediate and delayed recall. Binaural beat exposure within the Gamma frequency band has been linked to alterations in neural connectivity and increased attention during working memory tasks, while stimulation in the Beta frequency band has been associated with increased memory performance. However, there is a lack of direct comparison between the effects of exposure to High-Beta versus Gamma binaural beats on immediate and delayed recall performance. This study employs a Bayesian approach and a between-groups 3 (exposure condition) x 2 (task presentation format) x 2 (timing of exposure) experimental design to examine the effects of both High-Beta and Gamma binaural beats on immediate and delayed recall performance in 75 participants. The results show that exposure to binaural beats resulted in mixed effects, with exposure to Gamma binaural beats only having a significant impact on immediate recall when combined with visual presentation, and exposure to High-Beta binaural beats during encoding and recall potentially interfering with recalling semantic information such as story themes after a delay. Comparatively, High-Beta binaural beat exposure did not significantly improve memory performance, while exposure to Gamma binaural beats only showed a significant improvement in memory performance when participants recalled information from the auditory memory tasks. These results have important implications for research and clinical work focused on cognitive improvement.